THE IMPLEMENTATION OF GOOGLE MAP TO ENHANCE STUDENTS’ SPEAKING SKILL IN LEARNING ENGLISH AT YASIN 9 DARUSSALAM MODERN BOARDING SCHOOL - Sundari Tri Wahyuni (Langue (Journal of Language and Education), 2023)
The presence kinds of applications are paramount ways to enhance students learning of English, particularly students’ enthusiasts. In this case, the researcher used Google Map to improve students' speaking skills in learning English, as well as to describe the students' responses to this application. Google Maps is one of the media that can be used in English learning because it is a collaborative tool, interactive, and innovative way to increase students' visualization of English material. The design method used by the researcher was Classroom Action Research. The information was gathered from the seventh grade and who was learned using Google Maps. There were ten students in total. The study discovered that each cycle made more progress in terms of students’ participation. Students appeared to be excited about putting their existing insights to use. The improvement is significant, particularly in terms of students’ participation and performance. It was possible to see this by comparing the researcher's notes, student interviews, observation sheets, and student tasks from cycle to cycle three. The use of Google Maps as a learning medium contributes to providing an enjoyable learning medium in English teaching and learning. On the other hand, three students were not actively involved, two were redundant to English, and two had difficulty recognizing unfamiliar words. Nevertheless, in each cycle they show improvement; the students are motivated and there was a desire to learn. Keywords: Speaking Ability, Google Map, Application, Contextually.